Murder at Beaulieu Abbey - Clark, Cassandra (Clark, Cassandra. Abbess of Meaux mysteries, 2021)
"February, 1390. The Church seethes with rebellion. Newly elected Pope Boniface faces a challenger: the anti-pope Clement, who sows discord from his power base in France.The quarrel threatens the very survival of the Cistercian Order. So when suspicions grow that distant Beaulieu Abbey may turn traitor, Hildegard's prioress summons her with a mission she can't refuse: travel to the isolated royal abbey and spy out their true allegiance.The public reason for Hildegard's trip is more prosaic. A young Cornish heiress, promised in marriage to the son of local aristocrat Sir William, needs escorting to her new home. It's not often Hildegard joins a betrothal party, and she's looking forward to meeting the girl. But little does Hildegard know, death and danger wait at Beaulieu - and even the protection of her travelling companions, the monks militant Brother Gregory and Brother Egbert, may not be enough to keep her safe from harm . . ."--Publisher.